Runaway inflation in Chile, 1970-1973; Inflación descontrolada en chile, 1970-1973 - Sebastian Edwards (Estudios de Economía, 2024)
In this essay, I argue that the explosion of inflation during the Salvador Allende administration in Chile (above 1,500% on a six-month annualized measure) was predictable. The government's use of massive and strict price controls generated acute macroeconomic imbalances. I postulate that the combination of runaway inflation, shortages, and black markets generated major hostility among the middle class and that that unhappiness reduced the support for the Unidad Popular government.
Keywords: B22; E52; E58; F31; F33; 330; Socialism; Salvador Allende; devaluation; hyperinflation; Chile; price controls; Unidad Popular